ANALISIS POLA DISTRIBUSI DAN INTENSITAS CURAH HUJAN DI DAS BOLANGO BONE - Karim, Meldiana; Labdul, Barry Yusuf; Husnan, Rawiyah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2021)
Heavy precipitation is among the causes of flooding. Bone Bolango is one of the flooding areas in Gorontalo. Since the parameters determining the discharge of the flood is precipitation, an analysis method for determining the distribution pattern and precipitation that fits the situation in the watershed area of Bolango Bone is required. Thereby, the present study aimed at analyzing the distribution pattern and the precipitation in the area. The analysis methods of rainfall distribution were the normal, log-normal, log Pearson type III, and Gumbel methods. In addition, the precipitation was examined using Talbot method, Sherman method, and Ishiguro method. The data consisted of daily precipitation data (the data from the last 10 years at minimum) from Alale station, Boidu, Longalo, Dulamayo Selatan, and Sogitia Permata. According to the results of parameter statistical analysis, the value of Cs, Cv, and Ck of the precipitation in 5 stations did not meet the requirements for normal distribution, log-normal, and Gumbel. The Cv value of Alale station, Boidu station, Longalo station, Dulamayo Selatan station, and Sogitia station is 0.3, 0.32, 0.19, 0.23, and 0.28, respectively. The Cs value of those stations, in consecutive order, is 3.45, 2.21, 1.33, 0.92, and 1.11, and the Ck value is 18.58, 6.64, 4.55, 2.08, and 3.99. On that ground, the distribution pattern that best fits the watershed area of Bone Bolango us the Log Pearson III. Further, the most appropriate measurement of the precipitation in the area is the Sherman method. This method has the lowest standard deviation value at 67.3 mm and the best correlation value at 1. The heaviest rainfall occurred in the duration of 5 minutes and the return period of 100 years. The precipitation in Alale station, Boidu, Longalo, Dulamayo Selatan, and Sogitia is 378.15 mm/hr, 250.78 mm/hr, 188.98 mm/hr, 300.76 mm/hr, and 358.82 mm/hr, respectively.